2003
DOI: 10.1113/jphysiol.2002.032847
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to thyroid hormone increases Na+ current and intracellular Ca2+ in cat atrial myocytes

Abstract: Whole‐cell recording methods and fluorescence microscopy were used to study the effects of acute exposure to thyroid hormone (T3) on cat atrial myocytes. Acute exposure (≈5 min) to 10 nm T3 significantly increased tetrodotoxin (TTX)‐sensitive inward Na+ current (INa) at voltages between −40 and +20 mV. At maximal INa activation (−40 mV) T3 increased peak INa by 32 %. T3 had no effect on the time course of INa decay, voltage dependence of activation, inactivation, or recovery from inactivation. Comparable expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…Although there is increasing evidence of an important role for phosphorylation in TH signaling (Lin et al, 1997(Lin et al, , 1998(Lin et al, , 1999bSchmidt et al, 2002;Wang et al, 2003) in in vitro and in cultured mammalian cell lines, few studies have addressed its relevance during development in vivo. In this study, by using a tadpole tail organ culture system as an experimental model, we demonstrate the possible involvement of T 3 -induced PKC tyrosine phosphorylation, which regulates TR␣ phosphorylation, thereby affecting tail regression.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is increasing evidence of an important role for phosphorylation in TH signaling (Lin et al, 1997(Lin et al, , 1998(Lin et al, , 1999bSchmidt et al, 2002;Wang et al, 2003) in in vitro and in cultured mammalian cell lines, few studies have addressed its relevance during development in vivo. In this study, by using a tadpole tail organ culture system as an experimental model, we demonstrate the possible involvement of T 3 -induced PKC tyrosine phosphorylation, which regulates TR␣ phosphorylation, thereby affecting tail regression.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of correlation between the abundance of GLUT3 and GLUT4 and the insulin-stimulated glucose uptake in the monocytes of the HR patients could be attributed to elevated intracellular concentration of calcium. It has been recently shown that the elevated levels of T 3 in HR increase calcium concentration in the cytosol (28). Elevated levels of cytosolic calcium can modulate insulin's ability to desphosporylate GLUT4, thus reducing its intrinsic activity and resulting in calciuminduced insulin resistance (29).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the elevated cellular T 3 content can increase the cytosolic calcium concentration [26] that may cause a calcium-induced insulin resistin [27]. Furthermore, these patients are known to have significant elevation in the levels of resistin, an insulin antagonizing adipocytokine that may enhance the development of insulin resistance [28].…”
Section: Discussionmentioning
confidence: 99%